Competition in Signaling - Federico Vaccari (Fondazione Eni Enrico Mattei (FEEM), 2022)
I study a multi-sender signaling game between an uninformed decision maker and two senders with common private information and conflicting interests. Senders can misreport information at a cost that is tied to the size of the misrepresentation. The main results concern the amount of information that is transmitted in equilibrium and the language used by senders to convey such information. Fully revealing and pure-strategy equilibria exist but are not plausible. I first identify sufficient conditions under which equilibria are essentially unique, robust, and always exist, and then deliver a complete characterization of these equilibria. As an application, I study the informative value of different judicial procedures.
Keywords: C72; D72; D82; 330; Signaling; Multi-sender; Competition; Misreporting; Communication